2017
DOI: 10.15171/jnp.2018.37
|View full text |Cite
|
Sign up to set email alerts
|

Metformin with insulin relieves oxidative stress and confers renoprotection in type 1 diabetes in vivo

Abstract: Background: Oxidative stress and impaired antioxidant capacity in diabetes are associated with diabetic nephropathy. Metformin, as an adjunct to insulin could decrease oxidative stress and may therefore improve renal function in type 1 diabetes (T1D). Objectives: To investigate the effects of metformin as adds-on therapy to insulin on renal dysfunction in T1D. Materials and Methods: Male Sprague-Dawley rats (230-250 g) were divided into 5 groups (n =7). Rats in groups A and B were orally treated with 3.0 mL/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Our results therefore suggest that hyperglycaemia provoked increased expression of Nrf2 protein in diabetic rats but naringenin relieved the oxidative burden and obliterated the induction of Nrf2 protein expression which could have triggered the transcription of antioxidant enzyme systems. We have previously shown that hyperglycaemia is associated with increased oxidative stress in diabetic animals, [40] and our results obtained both in vitro and in vivo presented here therefore do corroborate the fact that hyperglycaemia-induced oxidative stress can be mitigated by naringenin which ultimately spares hepatocytes of the need to activate antioxidant defence systems. Our results should not be interpreted to suggest that naringenin does not activate Nrf2 protein expression leading to increased synthesis of endogenous antioxidant enzymes as has been previously reported.…”
Section: Discussionsupporting
confidence: 89%
“…Our results therefore suggest that hyperglycaemia provoked increased expression of Nrf2 protein in diabetic rats but naringenin relieved the oxidative burden and obliterated the induction of Nrf2 protein expression which could have triggered the transcription of antioxidant enzyme systems. We have previously shown that hyperglycaemia is associated with increased oxidative stress in diabetic animals, [40] and our results obtained both in vitro and in vivo presented here therefore do corroborate the fact that hyperglycaemia-induced oxidative stress can be mitigated by naringenin which ultimately spares hepatocytes of the need to activate antioxidant defence systems. Our results should not be interpreted to suggest that naringenin does not activate Nrf2 protein expression leading to increased synthesis of endogenous antioxidant enzymes as has been previously reported.…”
Section: Discussionsupporting
confidence: 89%
“…Metformin is involved in controlling oxidative stress by controlling complex I of the mitochondrial electron transfer chain (Kinaan et al 2015 ; Wiernsperger 2015 ) and can be effective in reducing kidney damage induced by gentamicin (Darabi and Hasanvand 2018 ; Hasanvand 2018 ). Many studies have shown that the anti-inflammatory and antioxidative stress effects of metformin in various diseases, such as rheumatoid arthritis, neuropathic pain, renal disorders and Ankylosing spondylitis (Son et al 2014 , Afshari et al 2018 , Driver et al 2018 , Qin et al 2018a , b , Rajaei, Haybar et al 2018 ). This effect of metformin is achieved via activating multiple signalling pathways, including AMPK and Pi3K/AKT.…”
Section: Ampk Metabolic and Non-metabolic Pathwaysmentioning
confidence: 99%